The Role Of Collective And Individual Training In Amir Temur’s Army - Fayziyev, Zavqiddin Xayrilloevich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article studies the military training practices which Amir Temur used in his 14th-15th century military forces to examine how collective training methods and individual training methods affected military personnel readiness. The research shows that the combination between strict personal skill training and team practice sessions produced an exceptional fighting unit which maintained battlefield supremacy throughout Central Asia and the Middle East for multiple decades.